Non-fractional and fractional mathematical analysis and simulations for Q fever - Asamoah, Joshua Kiddy K.; Okyere, Eric; Yankson, Ernest; Opoku, Alex Akwasi; Adom-Konadu, Agnes; Acheampong, Edward; Arthur, Yarhands Dissou (Elsevier, 2024)
This article is published by Elsevier 2022 and is also available at https://doi.org/10.1016/j.chaos.2022.111821